PROFESSIONAL IDENTITY FORMATION OF FOUR NOVICE ENGLISH TEACHERS - Tabita Melania Mustaka Weni (Widya Mandala Surabaya Catholic University, 2021)
Decisions and problems are two common things that are faced by novice English teachers in their transition time from being university students to a professional career as teachers. Decisions that are made and problems that are faced by novice English teachers might reveal how their professional identity is formed. This study is intended to explore how the stories that novice English teachers tell or share regarding their decisions in entering the career and the problems that they face form their professional identity. The participants in this narrative inquiry study were 4 novice English teachers who graduated from the English department, took part in teaching practice, and have been teaching for less than five years in schools after their graduation. The data of this study were in the form of narratives which were collected from the participants through the written and telephone interviews. The narratives were analyzed using thematic analysis and the identities were classified based on Karaolis and Philippou’s (2019) elements of professional identity. The findings show that decisions that were made by the novice English teachers formed their professional identity in four stages. They are before entering teaching, early stage, after a while in the profession, and current stage. The identities that are formed are in terms of their self-esteem, self-efficacy, professional commitment, job satisfaction, work motivation, task orientation, and future perspective. The identities are formed both in positive and negative ways. Furthermore, the problems that they faced formed their professional identity in terms of their self-esteem, self-efficacy, professional commitment, job satisfaction, and task orientation in positive and negative ways.